Micropropagation For Ficus Carica L. Cv. Panachee Using Light-Emitting Diodes System - Eyu, Chan Hong (2021)
Ficus carica L. is challenging and time-consuming through conventional plant propagation methods due to the low survival rate. This study aims to establish an optimised protocol using response surface methodology (RSM) for micropropagation and meristem culture on F. carica L. cv. Panachee under light-emitting diodes (LEDs) application using different spectra. In 3-significant factors by Box-Behken design (BBD) experiment, meristem culture was optimised by incubating meristematic tissue (0.5 – 1.0 mm) onto filter paper bridge partially soaked in liquid Murashige and Skoog (MS) medium supplemented with 50 μM zeatin (X1) under red LEDs at the intensity of 1.26 μ mol/s (X3) (Ymeristem*red = 0.882 + 0.271X1 - 0.250X3*red – 0.558X1X3*red). For micropropagation, 4-significant factors by BBD experiment were used to developed second-order mathematical models, which resulted in incomparable growth and development at different LED spectra. Optimised micropropagation protocols with every four-weeks interval for each stage can be integrated with a SMART LED system with the incubation on gelled MS added with 30 μM IAA (B) and 1.0 g/L activated charcoal (C) under the combination of red, green, and blue (RGB) LEDs at 22.20 μmol/s (DRGB) that resulted 1.88 shoots (Number of shoots RGB LED = 0.4148 + 0.1667B + 0.3000C + 0.2500C + 0.400BC + 0.350CDRGB). Subsequently, followed by optimisation through gelled MS fortified with 40 μM BAP (A), 30 μM IAA (B), and 1.0 g/L activated charcoal (C) under red LEDs to achieve the greatest height increment at 32.97 mm after four weeks (Final height red LED = 9.078 + 1.767A + 1.733B + 1.822C + 2.73A2 + 4.68B2 + 2.55AB + 2.95AC + 5.65BC).